Santri's Contribution in Realizing Inclusive Sharia Economic Acceleration - Mirza Avicenna Asyifyan (Indonesian Economic Review, 2023)
The aim of this research is to explain strategies for optimizing the role of santri in realizing inclusive sharia economic acceleration. A qualitative approach was chosen to explore informant responses in depth in their contribution to developing the sharia economy in Indonesia. Through in-depth interviews followed by data condensation, data presentation and conclusion drawing, it can be explained that to realize the acceleration of the sharia economy, inclusiveness is needed, namely by optimizing many parties or stakeholders, namely: the Ministry of Religion, Bank Indonesia and universities with their Tridharma of Higher Education. Meanwhile, the strategy used is to strengthen the knowledge and competence of students in the form of education and training.